Meningkatkan Pengelolaan Keuangan Umkm Kuliner Di Denpasar Melalui Gaya Hidup Dan Literasi Keuangan - Sri Wahyuni, Elviyana; Indiani, Ni Luh; Suparta, I Nyoman (Innovative: Journal Of Social Science Research, 2024)
This study included 99 businesses owned by UMKM Kuliner in Denpasar as a sample, with the aim of evaluating (1) the simultaneous impact of lifestyle and financial literacy, (2) the impact of lifestyle and financial literacy, and (3) the impact of financial literacy on the loan of UMKM Kuliner. This study is conducted in a quantitative manner, with data collected through observation and questionnaires. In this research, validity, reliability, and classical assumptions are used.The study's findings indicate that: (1) the lifestyle variable has an uji  value of 0.028 < 0,05, indicating that a parsimal lifestyle affects the amount of money that UMKM Kuliner in Denpasar charges; (2) the literate variable has an uji value of 0,000 < 0,05, indicating that a parsimal literate life affects the amount of money that UMKM Kuliner in Denpasar charges; and (3) the signifikansi uji F has a value of 0,000 < 0,05. For this reason, the hypothesis is put out that the exchange rate is negatively impacted by both lifestyle and financial literacy working together.